2018
DOI: 10.2146/ajhp170420
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an antiretroviral stewardship strategy on medication error rates

Abstract: An antiretroviral stewardship strategy for hospitalized HIV patients including prospective audit by staff pharmacists through use of an antiretroviral medication therapy checklist at the time of order verification decreased error rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…50 Shea et al demonstrated that the combination of prescriber education and pharmacist-led medication reconciliation was effective in reducing prescribing errors. 52 However, the combination of prescriber education and CPOE in the study by Daniels et al did not reduce prescribing errors. 48 Cann et al applied prescriber education (PE) and pharmacist partnership in an acute surgical ward, with no significant change in medication errors with 12.0 errors at pre-intervention and 10.9 errors per 100,000 patient hours [relative risk (RR) 0.92, 95% confidence interval (CI) 0.40-2.08, p = 0.835].…”
Section: Combining Intervention Typesmentioning
confidence: 90%
See 2 more Smart Citations
“…50 Shea et al demonstrated that the combination of prescriber education and pharmacist-led medication reconciliation was effective in reducing prescribing errors. 52 However, the combination of prescriber education and CPOE in the study by Daniels et al did not reduce prescribing errors. 48 Cann et al applied prescriber education (PE) and pharmacist partnership in an acute surgical ward, with no significant change in medication errors with 12.0 errors at pre-intervention and 10.9 errors per 100,000 patient hours [relative risk (RR) 0.92, 95% confidence interval (CI) 0.40-2.08, p = 0.835].…”
Section: Combining Intervention Typesmentioning
confidence: 90%
“…38 However, it is difficult to deduce the individual effect of prescriber education when combined with other interventions. 47,48,52,53 One cluster randomised trial investigated the effect of e-learning tools in comparison to pharmacists' targeted feedback and education. 38 In this study, prescribing errors showed no change in medication errors after prescribers finished e-learning modules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study reinforces the impact an HIV-trained clinical pharmacist can have on reducing inpatient medication error rates related to ART and OI medications. Previous studies have demonstrated the impact of pharmacist-led interventions on reductions in ART errors [ 2 , 17–20 , 27 ]. The value of a dedicated, multidisciplinary, ARV stewardship team has also proven benefit in reduction of inpatient ART medication error rates [ 7 , 9 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] Antiretroviral stewardship programs (ARVSPs) have been shown to decrease medication error rates and improve other outcomes. [15][16][17][18][19][20] This article reviews published literature on ARVSPs and provides guidance on key aspects of ARVSPs for those looking to implement programs at their institutions.…”
Section: Introductionmentioning
confidence: 99%